2009
DOI: 10.1590/s0034-89102009000900014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de diagnóstico auto-referido de osteoporose, Brasil, 2006

Abstract: OBJECTIVE:To estimate the prevalence of self-reported osteoporosis (with previous medical diagnosis) and the associated risk and protection factors. METHODS:A cross-sectional study was carried out, based on data from the system Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico (VIGITEL -telephone-based surveillance of risk and protective factors for chronic diseases). A total of 54,369 individuals aged ≥ 18 years living in homes served by at least one fi xed telephone lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
23

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 16 publications
3
16
0
23
Order By: Relevance
“…In addition, there was higher frequency of diagnosis of arterial hypertension in individuals with a lower level of education, as observed in other studies 25 . Data from the 2008 VIGITEL survey corroborate previous studies which have shown that osteoporosis primarily affects women after menopause and those with a lower level of education 26,27 . High alcohol use is described as a risk factor for hypertension, cirrhosis, cerebrovascular accident, and pharynx, larynx, esophagus and liver cancer.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, there was higher frequency of diagnosis of arterial hypertension in individuals with a lower level of education, as observed in other studies 25 . Data from the 2008 VIGITEL survey corroborate previous studies which have shown that osteoporosis primarily affects women after menopause and those with a lower level of education 26,27 . High alcohol use is described as a risk factor for hypertension, cirrhosis, cerebrovascular accident, and pharynx, larynx, esophagus and liver cancer.…”
Section: Discussionsupporting
confidence: 80%
“…Contuto, mesmo considerando o efeito da seleção pela mortalidade masculina, dado o grande diferencial nas prevalências, acredita-se que essas possam ser atribuídas principalmente às questões relacionadas à constituição corporal feminina, como as alterações hormonais pós-menopausa. [35][36][37] . Assim, as mulheres seriam mais acometidas por essa enfermidade, demandando atenção.…”
Section: ▄ Resultadosunclassified
“…A maior freqüência nas usuárias de planos de saúde, mesmo após ajuste de idade e escolaridade, poderia também ser explicada pela maior oportunidade de diagnóstico e não prevalência real 40 .…”
Section: Resultsunclassified
“…As operadoras de planos de saúde -empresas que estruturam, gerenciam e comercializam planos de saúde -atuam no Brasil desde a déca-da de 40. Daquela época até o final dos anos 90, houve baixa interferência do Estado na dinâmica de funcionamento do mercado, especialmente no que se refere aos modelos da atenção à saúde.…”
Section: Introductionunclassified